Community development projects and livelihoods in Lepelle-Nkumpi Municipality of Limpopo Province of South Africa - Nziane, E.M. (My University, 2009)
This study focuses on the impact of the community development projects on the livelihoods of the people. The aim of the study is to assess the impact of the community development projects and the livelihood of the community of Lepelle-Nkumpi Municipality. The study examines the operations and performance of the community development projects since they started. The objectives of the study are to assess the impact of the community development projects on the livelihood of the beneficiaries and the community in terms of income, jobs and living standards, as well as identify and recommend appropriate intervention strategies where necessary. The finding of the study revealed that the community development projects did have an impact on both job creation and income generation, although the income part of it is not satisfactory. The other findings were the skewed participation where women were dominating. The study reveals that the government and the private sector should play an active role in training the beneficiaries, encourage youth participation in order to ensure sustainability of the projects, and also expose the project members to different technologies available in agriculture to ensure mass productions which will translate into better incomes from the projects.
Thesis (M.Dev.) --University of Limpopo, 2009
Keywords: Community development; Economic growth; Poverty alleviation; Community development -- South Africa; Development projects